Curious old gravestones in and about Boston / selected by Walter Rowlands ; photographed by Howland Shaw Chandler. - Rowlands, Walter, 1855- compiler. (Tufts University. Tisch Library., 2019)
1 online resource (50 leaves of plates) : chiefly illustrations